UMPSA expands its cooperation network to Japan - Nor Salwana, Mohammad Idris (UMPSA, 2024)
TSU MIE, JAPAN, 27 June 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has taken a significant step in expanding its cooperation network to Japan by signing a memorandum of understanding (MoU) with Mie University.